Quality Analysis Of Cream Scrub Combination of Moringa (Moringa oleifera) Leaf Extract and White Glutinous Rice (Oryza sativa glutinosa) Starch - Jamilatun, Makhabbah; Rahmadianty, Harmayanti Aidha; Lukito, Pradea Indah (PT. Riset Press International, 2023)
Premature aging is a health problem that attacks facial skin and is very disturbing appearance. This can be overcome of them with antioxidant compounds. Sources of natural antioxidant compounds in Indonesia are found in Moringa leaves and white glutinous rice. The use of antioxidants is facilitated by making them into cosmetic preparations, one of which is scrub cream. This study aims to determine the physical quality and antioxidant activity of a cream scrub combined with Moringa leaf extract and glutinous rice starch. This research begins with the extraction of moringa leaves and white glutinous rice starch. Moringa leaf extract and white glutinous rice starch obtained were then made into cream scrub preparations at 4 concentration variations, with a comparison of Moringa leaf extract and white glutinous rice starch F0 (0%:0%), F1 (25%:75%), F2 ( 50%:50%) and F3 (75%:25%). The quality test of the luxurious cream included an organoleptic test, pH test, spreadability test, adhesion test, and irritation test. An antioxidant activity test was carried out using the DPPH method. The results showed that the combination of Moringa Leaf Extract (Moringa oleifera) and White Glutinous Rice Starch can be formulated as a cream scrub, with the results of physical quality both organoleptic, pH, spreadability, adhesion, and irritation fulfilling the requirements, and antioxidant activity in the strong category at F3.